Experts warn Nepal Government not to reduce local public health spending - Simkhada, P.; Teijlingen, E.; Simkhada, B.; Regmi, P.; Aryal, N.; Marahatta, S.B. (Journal of Manmohan Memorial Institute of Health Sciences, 2018)
No abstract available. JMMIHS.2018;4(1):1-3